Recent Progress of Nano-drug Combined with Chimeric Antigen Receptor T Cell Therapy in the Treatment of Soild Tumors - Yi LIU; Ning LI; Wenyang JIANG; Qing GENG (Chinese Journal of Lung Cancer, 2023)
Chimeric antigen receptor T cell (CAR-T) therapy has shown remarkable success in treating hematological malignancies. However, CAR-T therapy for solid tumors is still limited due to the unique solid-tumor microenvironment and heterogeneous target antigen expression, which leads to an urgent need of combining other therapies. At present, nano delivery system has become one of the most promising directions for the development of anti-tumor drugs. Based on the background of CAR-T and tumor treatment, we focus on the research progress of nanomedicine combined with CAR-T therapy, and systematically review the strategies and examples in recent years in the aspects of in vivo delivery of mRNA, regulation of tumor microenvironment, combination with photothermal therapy. And we also look forward to the future direction of this filed.